Kepemimpinan Terhadap Perempuan (Respon Feminisme Terhadap Qowwâmah) - Ja’far Shodiq (Universitas Darussalam Gontor, 2017)
According to the view of muslim feminists towards Qawwâmah, male and female are equal in all aspects of life. The difference is only in taqwa. According of them, it’s not Qawwam if the male is not capable in showing the capability, but according to the view of the mufasirs, Qawwâmah is to lead, to educate, defend, maintain and guide to uprightness. According to the analysis and thought comparison, the feminists rejected the concept of male leadership of women, indirectly because of their assumption that leadership is not entitled to males but can also be taken up by the female. While the muffasirs interpret the verse as the male as absolute leader of the female, either in domestic, ritual and social.